PTU-248 A specialist cirrhosis clinic improves screening, patient satisfaction and attendance of patients with advanced liver disease. (28th May 2012) - Fenton, N K; Khan, S A; Marcinkowski, H; Cowan, M L
Abstract : Introduction: Cirrhosis represents the end stage of progressive liver disease and is associated with potentially lethal complications. Early detection and management of these complications can improve outcome. In July 2008, a dedicated Cirrhosis Clinic was instigated at St. Mary's Hospital, London, with the aim of enhancing the standard of care by improving the diagnosis and management of liver complications. We investigated the clinical impact of this novel clinic dedicated for patients with cirrhosis. Methods: We compared the demographics, clinical outcomes and patient satisfaction among 50 patients attending the Cirrhosis Clinic and 30 patients with cirrhosis attending a general Hepatology outpatient clinic. Clinical information and rates of screening for complications were assessed from the case notes and the hospital databases. Attendance rates were collected prospectively and patient satisfaction assessed with a standardised questionnaire. Results: The mean age, gender and ethnicity of patients in the Cirrhosis Clinic were identical to those in the general Hepatology clinic (57 years; 70% male; 62% Caucasian). Patients in the Cirrhosis Clinic were more likely to have alcoholic liver disease (58% vs 23%; p<0.05). Cirrhosis Clinic patients were more likely to have ascites (56% vs 17%; p<0.05), varices (60% vs 26%; p<0.05), encephalopathy (20% vs 3%; p<0.05), Child stage B or C (52% vs 19%; p<0.05) and had higher UKELD (47 vs 43; p<0.05). Screening rates were higher in the Cirrhosis Clinic patients for hepatocellular carcinoma (70% vs 57%; p<0.05), vitamin D deficiency (86% vs 40%; p<0.05) and varices (90% vs 77%; p=0.11). Attendance rates in the Cirrhosis Clinic improved substantially after the introduction of a telephone reminder (86% vs 64%; p<0.05). Attendance rates were better than the general clinic (86% vs 77%) but this was not statistically significant (p=0.27). The Cirrhosis Clinic was rated excellent by 67% of patients vs 34% of patients in the general clinic (p=0.06). Conclusion: A dedicated clinic serving patients with cirrhosis improved screening rates for complications, boosted attendance rates and led to increased patient satisfaction. Further work is required to evaluate the impact on long-term outcomes and cost-effectiveness. Competing interests: None declared.